Job Satisfaction Among Employees After a Merger: A Cross-Sectional Survey in the Local Health Unit of Sardinia Region, Italy - Isonne, Claudia; Nardi, Angelo; de Soccio, Pasquale; Zerbetto, Alessandro; Giffi, Monica; Sindoni, Alessandro; Marotta, Daniela; Baccolini, Valentina; Migliara, Giuseppe; Mete, Rosario; Marzuillo, Carolina; Villari, Paolo; et al. (Frontiers in Public Health, 2021)
Job satisfaction plays an important role in healthcare organization and management; it is critical for maintaining and improving staff efficiency and consequently the quality of care provided. Organizational restructuring processes, including mergers, are likely to affect job satisfaction levels, but evidence of the impact they have is surprisingly scarce. The aim of the study was to describe a methodology used to measure job satisfaction of the employees at a Local Health Unit (LHU) in Italy immediately after a merger and to assess the determinants associated with any reduction in worker satisfaction. The study was conducted among employees of the LHU of the Sardinia Region in July 2018, after a merger of eight subregional LHUs had taken place. The entire staff was enrolled, of which a total of 1,737 employees were surveyed. We used a questionnaire exploring socio-demographic and working characteristics of the employees, the various areas related to job satisfaction and interviewee opinions on the merger process. Multivariable stepwise backward logistic regression models were built to identify factors independently associated with lower job satisfaction. The results of a multivariable analysis showed that lower job satisfaction was more likely in employees with an administrative role (aOR: 2.34, 95% CI: 1.37–4.00) or a career demotion (aOR: 1.84, 95%CI: 1.11–3.03). High levels of mental stress were strongly associated with lower job satisfaction (aOR: 5.64, 95%CI: 4.16–7.64). “More equity of employee rewards” was the only example of a set of responder suggestions found to be associated with lower job satisfaction (aOR: 2.30, 95%CI: 1.51–3.47). Generally, responders showed a good level of job satisfaction—and this was also the case following the merger—but some job profile determinants were strongly associated with low employee satisfaction. The results of the study highlighted several challenging areas and critical issues relating to working conditions. Further surveys are required to confirm these results and to monitor their evolution over time.